The cross & the crescent : an interfaith dialogue between Christianity and Islam - Dirks, Jerald (Beltsville, Md. : Amana Publications, 2001)
Drawing on his seminary education and thirty years of interaction with Muslims in America and overseas, the author digs deep into the roots of Christianity to bring out obscure information that highlights what was once common between Christianity and Islam.
Chapter 1 Parallels between Christianity and Islam 1 -- Chapter 2 Judaism, Christianity and Islam--Origins and Relationships 17 -- Chapter 3 The Books of Revelation and Scripture--A Comparison of Judaism, Christianity, and Islam 41 -- Chapter 4 The Baptism of Jesus--The Origin of the "Sonship" of Jesus 65 -- Chapter 5 The Crucifixion--A Question of Identity 77 -- Chapter 6 The Mission and Ministry of Jesus 113 -- Chapter 7 One Size Fits All--The Matthean Use of Prophecy 131 -- Chapter 8 The Prophet Job (Ayyoub) 163 -- Chapter 9 A Concise Introduction to Islam--Articles of Faith and Pillars of Practice 177.
Includes bibliographical references (pages 251-260).
Keywords: Islam -- Relations -- Christianity; Christianity and other religions -- Islam; Christianity; Interfaith relations; Islam; Islam; Christendom